Gaya Bahasa dalam Kumpulan Puisi “Dear You” Karya Moammar Emka - Nur Syamsiyah; Farida Yufarlina Rosita (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
The purpose of this study is to describe the types of use of language style in the collection of poems of “Dear You” by Moammar Emka published in 2011. This study uses descriptive qualitative methods. The data source in this study is a collection of poems contained in the poem “Dear You” by Moammar Emka. Data collection techniques in research, using content analysis techniques (text). The results of this study indicate that the use of language style and the value of character education in the collection of poetry “Dear You” by MoammarEmka has a type of language style: (a) parables, (b) metaphors, (c) personification, (d) depersonification, (e) hyperbole, (f) litotes, (g) metonimia, (h) sinekdoke, (i) alliteration, and (j) asonance. Of the ten language styles, the data obtained were 117 data with the smallest data of four data, namely the style of asonance language and the most data of thirty-four data, namely the style of the metaphorical language.